MET Gene High Copy Number (Amplification/Polysomy) Identified in Melanoma for Potential Targeted Therapy. Issue 4 (7th October 2021) - Ramani, Nisha S; Morani, Ajaykumar C; Zhang, Shengle
Abstract: Objectives: Aberrant expression of the mesenchymal epithelial transition factor ( MET ) gene has been observed in several malignancies, and drugs targeting the MET gene have been implicated in clinical trials with promising results. Hence, MET is a potentially targetable oncogenic driver. We explored the frequency of MET gene high copy number in melanomas and carcinomas. Methods: The study group included 135 patients. Tissue microarrays were constructed with 19 melanomas and 116 carcinomas diagnosed from 2010 to 2012. We screened MET gene copy number by fluorescence in situ hybridization analysis using probes for MET gene and CEP7 as control. Results: We found MET gene amplification in 2 (11%) of 19 melanoma cases, whereas 5 (26%) of 19 melanoma cases showed polysomy. For carcinomas, there was no MET gene amplification identified. However, 8 (7%) of 116 cases showed polysomy. Conclusions: In our study, MET gene amplification was identified in 11% of melanomas and is relatively concordant with few reported studies. However, about 26% of the additional melanoma cases showed MET gene polysomy, which has not been reported as per our knowledge. If these results are validated with further orthogonal studies, more of the melanoma cases could potentially benefit from targeted therapy with MET tyrosine kinase inhibitors.